Ethics of assertive care in mental health: A gradual concept - Liégeois, Axel (Frontiers in Psychiatry, 2023)
Mental health professionals have a contradictory social mission: respecting the autonomy of persons with mental illness while at the same time providing them with unsolicited or assertive care when necessary. The aim of this contribution is therefore to reflect on the ethical question of how care professionals can provide assertive care in an ethically responsible manner. To answer this question, we take a relational view of human beings, draw on the Ethics Committee for Mental Health Care of the Organisation Brothers, and invoke a case to shape the ethical reflection. In a relational view, assertive care starts by building a relationship of trust between the care partners: car users, next of kin and care professionals. We can distinguish different forms of assertive care based on the degree of decision-making capacity and the responsibility of the care users. The first two degrees of assertive care occur when care users are still fully capable of making decisions about care and of taking own responsibility: the care professionals [1] make themselves available for possible care, or [2] inform about possible care in the most objective way possible. When care users are partially capable of decision-making, the care partners share responsibility in six possible degrees of assertive care: the professionals [3] advise on possible care, [4] negotiate good care, [5] attract into assertive care, [6] persuade to assertive care, or exert [7] external or [8] internal pressure. If care users are completely incapable of decision-making in care, the care professionals and next of kin take on vicarious responsibility in two degrees of assertive care: the professionals [9] take over the care, or [10] carry out coercion. Which degree of assertive care is most appropriate must be considered in each situation. Criteria for determining the appropriateness of assertive care are the degree of decision-making capacity of the care users and the degree of the threat and seriousness of harm. As the threat of serious harm increases and the care users’ decision-making capacity decreases, forms of assertive care with a more freedom-restricting character are ethically justifiable.